The Affordable Care Act Medicaid expansion and interstate migration in border regions of US States - Friederike Seifert (Review of Regional Research, 2022)
In the wake of the Affordable Care Act, some US states expanded Medicaid eligibility to low-income, working-age adults while others did not. This study investigates whether this divergence induces migration across state borders to obtain Medicaid, especially in border regions of expansion states. It compares border with interior regions' in-migration in the concerned subgroup before and after the Medicaid expansion in linear probability difference-in-difference and triple difference regression frameworks. Using individual-level data from the American Community Surveys over 2012–2017, this study finds only a~statistically significant increase in in-migration to border regions after the expansion in Arkansas. The differing results across states could stem from statistical power issues of the employed regression analysis but might also result from state peculiarities. In Arkansas, the odds of having migrated increase by about 48% in its border regions after the Medicaid expansion compared to before and control regions. If all additional migrants take up Medicaid, the number of Medicaid beneficiaries in these regions increases by approximately 4%. Thus, even if the induced migration is statistically significant, it appears unlikely to impose meaningful fiscal externalities at the regional level.
Keywords: H5; H75; I13; R23; 910; Affordable Care Act; Medicaid expansion; Interstate migration; Border analysis; USA